Penerapan Pembelajaran Berbasis Inquiry pada Materi Elektrokimia terhadap Pemahaman Konseptual, Model Mental dan Sikap Siswa - Dwivelia Aftika Sari (Chemistry Education Department of Education and Teaching Faculty, 2021)
The purpose of this article review is to know the effect of applying inquiry-based learning on electrochemistry material to conceptual understanding, mental model and student attitudes. Based on some articles that have been reviewed, it can be concluded that the application of inquiry-based learning can improve conceptual understanding, mental model and positive attitude of students on electrochemistry material. The 5E inquiry (Engagement, Exploration, Explanation, Elaboration, and Evaluation) can be combined with the galvanic cell kit model to improve students' understanding of electrochemistry at the submicroscopic (molecular) level. Inquiry-based learning can be applied in both laboratory activities and classroom learning processes. The students' understanding of chemistry will be intact if students are able to connect the three levels of chemical representation.